GENE ACTIONS OF TRAITS CONTRIBUTING TO LODGING RESISTANCE IN WHEAT (Triticum aestivum L) (Bangladesh Journal of Plant Breeding and Genetics, 2007)
Estimates of gene action for lodging related traits at Wheat Research Center during 1999-2002 in three crosses of wheat showed different genetic control of the traits among the crosses. For almost all traits, additive or dominance effects or both components were significant in either three- or six-parameter model, indicating that both additive and dominance gene effects were operative for different traits contributing to lodging resistance. Although duplicate type of epistasis was also observed for second internode breaking strength, plant height and spikes per plant and grain yield per plant once in different crosses, additive x additive epistasis along with additive gene action for the aforesaid traits would improve selection of the same in the segregating populations. The additive x dominance gene interaction for second internode length, diameter and wall thickness would be useful too for improvement of second internode breaking strength and consequently lodging resistance, as their inheritance and selection in segregating populations would be relatively easier than the traits controlled by completely non-additive genes. For duplicate type of epistasis biparental mating or recurrent selection followed by conventional selection is suggested.DOI: http://dx.doi.org/10.3329/bjpbg.v20i2.17031